1975
DOI: 10.1192/bjp.126.2.127
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study of Infantile Autism and Specific Developmental Receptive Language Disorder

Abstract: There is now extensive evidence that autistic children manifest a specific cognitive defect involving language impairment (Rutter, 1974). The presence of such a deficit is demonstrated by the pattern of clinical findings (Rutter, 1968; Rutter, Bartak and Newman, 1971), the long term course of the disorder (Rutter, 1970), and the results of systematic experimental studies (Hermelin and O'Connor, 1970). Nevertheless, basic questions remain concerning the meaning of this deficit for theories on the nature and cau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
270
6
10

Year Published

1978
1978
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 542 publications
(300 citation statements)
references
References 44 publications
14
270
6
10
Order By: Relevance
“…Some studies have shown that children with HFA have equivalent or more severe difficulties with the structural aspects of language than children diagnosed with language impairments [e.g. Bartak, Rutter & Cox, 1975], while other studies have shown that some children with SLI have significant pragmatic language difficulties in the absence of social deficits [e.g. Bishop & Norbury, 2002].…”
Section: Motor Difficulties In Children With Specific Language Impairmentioning
confidence: 99%
“…Some studies have shown that children with HFA have equivalent or more severe difficulties with the structural aspects of language than children diagnosed with language impairments [e.g. Bartak, Rutter & Cox, 1975], while other studies have shown that some children with SLI have significant pragmatic language difficulties in the absence of social deficits [e.g. Bishop & Norbury, 2002].…”
Section: Motor Difficulties In Children With Specific Language Impairmentioning
confidence: 99%
“…Children with AD, language disorders and DCD are delayed in achieving motor milestones (4). About 40% of AD children show gross motor problems, and about 30% show fine motor problems (2 22).…”
Section: Motor Coordinationmentioning
confidence: 99%
“…DCD children have poor visuo-spatial skills (46), are more impaired on performance than verbal intelligence tasks (25), and underachieve educationally (13 20). Highfunctioning AD children and RELD children are comparable on non-verbal tests (4). On verbal tests, the two groups do not consistently differ (31 65).…”
mentioning
confidence: 98%
“…Because the goals of these studies were to identify unique features of language in autism-features that distinguish between autism and other populations-they generally included matched groups of children with autism and some other comparison group or groups. Comparison groups included children with other language disorders, mental retardation, or typically developing children (e.g., Bartak, Rutter, & Cox, 1975, 1977 define autism or autism spectrum disorders, it is doubtful that across studies the same criteria were used for including children under the diagnostic label of "autism." These diagnostic issues began to be overcome in recent studies through reaching a consensus in both the clinical and research communities about how to define autism and associated disorders (APA, 1994;WHO, 1993) and through the introduction of gold standard methods for achieving reliable diagnoses using the Autism Diagnostic Interview-Revised version (ADI-R; Lord et al, 1994) and the Autism Diagnostic Observation Schedule (ADOS; Lord et al, 2000).…”
Section: Classic Studies Of Language In Autismmentioning
confidence: 99%